AB0669 The eular systemic sclerosis impact of disease (SCLEROID) score – a new patient-reported outcome measure for patients with systemic sclerosis – preliminary results from the ongoing validation study. (15th June 2017) - Dobrota, R; Becker, M; Fligelstone, K; Fransen, J; Kennedy, A; Allanore, Y; Carreira, P; Czirjak, L; Denton, C; Hesselstrand, R; Sandqvist, G; Kowal-Bielecka, O; et al.
Abstract : Background: Patient reported outcome measures (PROM) are required as key outcomes in therapeutic trials in systemic sclerosis (SSc). Given the unmet need of a validated, comprehensive PROM in SSc, the ScleroID questionnaire was developed by a team of patients with SSc and medical experts in the field. This is intended as a brief, disease-specific, patient-derived, disease impact score for scientific and clinical use in SSc. Objectives: To present a preliminary analysis from the ongoing ScleroID validation study. Methods: This EULAR-endorsed project involves 11 European centers specialized in SSc. Patients fullfilling the ACR/EULAR 2013 criteria were prospectively included since 05/16 in the ongoing observational cohort study. Patients filled in the ScleroID questionnaire (Figure 1 ), as well as selected comparators SHAQ, EQ5D, SF36. Additionally, they weighted the 10 dimensions of the ScleroID by distributing 100 points according to the perceived impact on their health. The final score calculation will be based on the ranking of the weights. The study includes a reliability arm (follow-up questionnaire 7–10 days from baseline), as well as a longitudinal arm, looking at sensitivity to change at follow-up visits after 6 and 12 months from baseline. Results: As of 01/2017 the study cohort included 224 patients with valid baseline data, 44 also had a reliability visit and 6 a 6-months follow-up visit. 84.4% of patients were female, 54.4% had limited SSc, median age 58, and median disease duration 8 years. The highest preliminary median weights for ScleroID domains were for Raynaud, impaired hand function, fatigue and pain (Table 1 ). Except for pain, these dimensions were also scored most highly in the ScleroID questionnaire at baseline. Conclusions: The EULAR ScleroID score is a novel tool designed for use in clinical practice and clinical trials to display the disease impact of SSc. In this preliminary analysis, Raynaud syndrome, impaired hand function, and fatigue were the main patient reported drivers of disease impact, however, further recruitment and validation of this new instrument is ongoing. Disclosure of Interest: R. Dobrota: None declared, M. Becker: None declared, K. Fligelstone: None declared, J. Fransen: None declared, A. Kennedy: None declared, Y. Allanore Grant/research support from: Grant/research support from: Bristol-Myers Squibb, Roche/Genentech, Inventiva, Pfizer, Sanofi, and Servier, Consultant for: Actelion, Bayer, Roche/Genentech, Inventiva, Medac, Pfizer, Sanofi, Servier, and UCB, P. Carreira: None declared, L. Czirjak: None declared, C. Denton: None declared, R. Hesselstrand: None declared, G. Sandqvist: None declared, O. Kowal-Bielecka: None declared, M. Matucci Cerinic: None declared, C. Mihai: None declared, A. Gheorghiu: None declared, U. Müller-Ladner: None declared, M. Vonk: None declared, T. Heiberg: None declared, O. Distler Grant/research support from: 4 D Science, AbbVie, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, iQone Healthcare, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm and Sinoxa, Consultant for: 4 D Science, AbbVie, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, iQone Healthcare, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm and Sinoxa